Kepentingan Nasional Indonesia Menjadikan Kawasan Kars Gunung Sewu Sebagai Unesco Global Geopark Network (GGN) - Rahadyan Arka Shunu; Anna Yulia Hartati (Kajian Hubungan Internasional, 2021)
This research is a contemporary study that addresses Indonesia's national interests to make Gunung Sewu a UNESCO Global Geopark Network. Global Geopark Network is a network with the name UNESCO that has a role to preserve the geological heritage and promote sustainable development in the community. Whereas Gunung Sewu is a karst region that is rich in tourism potential and geological heritage. In this study, the author focuses on the importance of the basic Indonesia to make Gunung Sewu the Global Geopark Network. The researcher used Felix Oppenheim's theory of national interests which stated that national interests were the ideals or goals of the state to prosper. As well as perspective from Joshua Goldstein that in order to achieve the goals of a country, a country cooperates with other parties. Based on the analysis and data, it is known that the national interests that Indonesia wants to achieve are our economic interests, namely increasing state revenues from the tourism sector and conservation interests to preserve the nature of mountain waste for the survival of the community.